APPROACHES TO THE ASSESSMENT OF SMALL INDUSTRIAL ENTERPRISES READINESS FOR THE DIGITAL ECONOMY - N. A. Orlova (Вестник университета)
One of the most relevant issues in the development of enterprises is their adaptation in the context of the transition to the digital economy. Despite the fact that today the speed of digital transformation of many Russian companies is much lower than in whole the world, digitalization has a number of undeniable advantages. An analysis of existing approaches to digital maturity assessment is one of the first steps on the way to the transition of the enterprise to Industry 4.0. The main approaches to the assessing the readiness of enterprises to the digital economy have been considered. Their comparative analysis has been carried out, applicability and advantages of these approaches as the basis for the development and scaling of small manufacturing enterprises have been evaluated.